2013
DOI: 10.1242/dmm.011338
|View full text |Cite
|
Sign up to set email alerts
|

Hooked on fat: the role of lipid synthesis in cancer metabolism and tumour development

Abstract: An increased rate of lipid synthesis in cancerous tissues has long been recognised as an important aspect of the rewired metabolism of transformed cells. However, the contribution of lipids to cellular transformation, tumour development and tumour progression, as well as their potential role in facilitating the spread of cancerous cells to secondary sites, are not yet fully understood. In this article, we review the recent findings that support the importance of lipid synthesis and metabolism in tumorigenesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

17
679
0
10

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 662 publications
(706 citation statements)
references
References 111 publications
17
679
0
10
Order By: Relevance
“…Together, these observations imply that HspA1A-membrane association would be increased in membrane regions enriched in saturated lipids, such as lipid rafts, and in cellular membranes containing a high number of saturated lipids. These suggestions are consistent with the presence of HspA1A and other Hsp70s at the plasma membrane of stressed and cancer cells, which have increased membrane rigidity (Baenke et al 2013;De Maio 2014;Kirkegaard et al 2010;Lancaster and Febbraio 2005a;Mambula et al 2007;Multhoff 2007;Schilling et al 2009). Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Together, these observations imply that HspA1A-membrane association would be increased in membrane regions enriched in saturated lipids, such as lipid rafts, and in cellular membranes containing a high number of saturated lipids. These suggestions are consistent with the presence of HspA1A and other Hsp70s at the plasma membrane of stressed and cancer cells, which have increased membrane rigidity (Baenke et al 2013;De Maio 2014;Kirkegaard et al 2010;Lancaster and Febbraio 2005a;Mambula et al 2007;Multhoff 2007;Schilling et al 2009). Fig.…”
Section: Discussionsupporting
confidence: 82%
“…Glioblastoma spheroids harbor hypoxic cores where metabolic pathways, including those involving lipids, are changed [4,[83][84][85]. De novo lipogenesis, for instance, was shown to be bypassed in cancer cells in hypoxic conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Although otherwise highly heterogeneous, most cancer types present a lipogenic phenotype characterized by the upregulation of key enzymes and transcriptional factors controlling lipid metabolism (e.g. Akt, fatty acid synthase, hypoxia-inducible factor 1-alpha, sterol regulatory element binding proteins, acetyl-CoA carboxylase alpha), and a boost in de novo lipogenesis [2][3][4][5]. In solid malignancies, the hypoxic conditions found at the core of the tumors induce adaptive pathways aimed at maintaining lipid synthesis, homeostatic pH and cell survival [6].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 In addition, lipid biosynthesis is altered in cancer cells, thus affecting the lipid species present. [5][6][7] In fact, it has been shown that tumors not only harbor structurally different lipids compared to normal cells, but also, in several cases, accumulate fatty acids, cholesterol, and phospholipid species. [5][6][7] Thus, it is plausible that self-lipid-reactive T cells could contribute to antitumor immunity through either recognizing novel tumor lipids or responding to accumulated self-lipids.…”
Section: Introductionmentioning
confidence: 99%